2022
DOI: 10.3390/jcm11041085
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Stone Protein: Review of a New Biomarker in Sepsis

Abstract: Sepsis is a life-threatening syndrome characterized by a dysregulated host response to an infection that may evolve rapidly into septic shock and multiple organ failure. Management of sepsis relies on the early recognition and diagnosis of infection and the providing of adequate and prompt antibiotic therapy and organ support. A novel protein biomarker, the pancreatic stone protein (PSP), has recently been studied as a biomarker of sepsis and the available evidence suggests that it has a higher diagnostic perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 62 publications
(68 reference statements)
0
13
0
1
Order By: Relevance
“…However, their values for identifying abdominal sepsis have yielded conflicting results [ 6 ]. A recent literature review [ 7 ] of 23 studies including a prospective multi-center study [ 4 ] and a meta-analysis [ 8 ] suggests that PSP has a higher diagnostic performance for the identification of infection and sepsis than the most used available biomarkers. The multi-center study shows that serial routine PSP measurement has the potential of ‘pre-symptomatic diagnosis of sepsis’ up to 72 h in advance with an optimal PSP cut-off of 290 ng/ml [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, their values for identifying abdominal sepsis have yielded conflicting results [ 6 ]. A recent literature review [ 7 ] of 23 studies including a prospective multi-center study [ 4 ] and a meta-analysis [ 8 ] suggests that PSP has a higher diagnostic performance for the identification of infection and sepsis than the most used available biomarkers. The multi-center study shows that serial routine PSP measurement has the potential of ‘pre-symptomatic diagnosis of sepsis’ up to 72 h in advance with an optimal PSP cut-off of 290 ng/ml [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…is was consistent with our study. ere have been many research studies looking for markers for the diagnosis and treatment of sepsis, including microRNAs, long noncoding RNAs, circular RNAs, pancreatic stone protein, and lipopolysaccharide-binding protein [26][27][28][29][30]. In our research, we identified 15 major hub genes (CCL5, CCR7, CD2, CD27, CD274, CD3D, GNLY, GZMA, GZMH, GZMK, IL2RB, IL7R, ITK, KLRB1, and PRF1) in the PPI network, and all of them were downregulated genes in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…PSP accuracy for the diagnosis of infection and sepsis among a wide spectrum of clinical settings seems to be, at least, comparable to the other classical biomarkers currently used in clinical practice. Furthermore, it seems to outperform those biomarkers in the prediction of sepsis, accounting for its earlier relative increase before clinical diagnosis, and it adds prognostic value [32,33]. PSP is a promising biomarker to diagnose infections in hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%